Naturalizing sensemaking - Snowden, Dave (Informed by Knowledge: Expert Performance in Complex Situations, 2010)
The focus of this book is on how experts adapt to complexity, synthesize and interpret information in context, and transform or "fuse" disparate items of information into coherent knowledge. The chapters examine these processes across experts (e.g. global leaders, individuals in extreme environments, managers, police officers, pilots, commanders, doctors, inventors), across contexts (e.g. space and space analogs, corporate organizations, command and control, crisis and crowd management, air traffic control, the operating room, product development), and for both individual and team performance. Successful information integration is a key factor in the success of diverse endeavors, including team attempts to climb Mt. Everest, crowd control in the Middle East, and remote drilling operations. This volume is divided into four sections, each with a specific focus on an area of expert performance, resulting in a text that covers a wide range of useful information. These sections present well-researched discussions, such as: the management of complex situations in various fields and decision contexts; technological and training approaches to facilitate knowledge management by individual experts and expert teams; new or neglected perspectives in expert decision making; and the importance of ‘modeling’ expert performance through techniques and frameworks such as Cognitive Task Analysis, computational architectures based on the notion of causal belief mapping such as ‘Convince Me,’ or the data/frame model of sensemaking. The volume provides essential reading for researchers and practitioners of Naturalistic Decision Making and those who study Expertise; Organizational and Cognitive Psychologists; and researchers and students in Business and Engineering.

SPACES MERL: Systems and Complexity White Paper - USAID (2016)
The Strategic Program for Analyzing Complexity and Evaluating Systems (SPACES MERL) project is an activity funded by USAID’s Global Development Lab and the Bureau for Policy, Planning and Learning (PPL). This three-year activity aims to bring a variety of tools and methodologies that decision-makers can use (alone or in combination) to provide comprehensive systems analysis. The activity is being implemented from 2015 to 2018 by a consortium of organizations expert in systems and complexity, including the Global Obesity Prevention Center (GOPC) at Johns Hopkins University (Prime), Global Knowledge Initiative (GKI), LINC and ResilientAfrica Network (RAN). This Systems and Complexity White Paper is a collaborative effort of the SPACES MERL team, designed to frame the international development landscape, with particular reference to USAID-funded activities, for application of systems and complexity approaches to design, monitoring and evaluation. Customized to the systems and complexity layperson with in-depth knowledge of international development practice, the objectives of this white paper are three-fold:  Provide an overview of systems and complexity practice, its current state of application and relevance to international development practice;  Establish a taxonomy of systems and complexity tools, highlighting the fit of those offered by SPACES MERL within the wider landscape; and  Review and provide information on application of SPACES MERL tools, their purpose and construction, required data, and their applicability to specific contexts.